Citrus tristeza virus: Evolution of Complex and Varied Genotypic Groups - Harper, Scott J. (Frontiers in Microbiology, 2013)
Amongst the Closteroviridae, Citrus tristeza virus (CTV) is almost unique in possessing a number of distinct and characterized strains, isolates of which produce a wide range of phenotype combinations among its different hosts. There is little understanding to connect genotypes to phenotypes, and to complicate matters more, these genotypes are found throughout the world as members of mixed populations within a single host plant. There is essentially no understanding of how combinations of genotypes affect symptom expression and disease severity. We know little about the evolution of the genotypes that have been characterized to date, little about the biological role of their diversity and particularly, about the effects of recombination. Additionally, genotype grouping has not been standardized. In this study we utilized an extensive array of CTV genomic information to classify the major genotypes, and to determine the major evolutionary processes that led to their formation and subsequent retention. Our analyses suggest that three major processes act on these genotypes: 1. ancestral diversification of the major CTV lineages, followed by 2. conservation and co-evolution of the major functional domains within, though not between CTV genotypes, and 3. extensive recombination between lineages that have given rise to new genotypes that have subsequently been retained within the global population. The effects of genotype diversity and host interaction are discussed, as is a proposal for standardizing the classification of existing and novel CTV genotypes.